DOES COPING MATTER? COPING AND CHRONIC PHYSIOLOGICAL DISTRESS AMONG AGING U.S. BLACK AND WHITE MEN. (11th November 2018) - Allen, J; Watkins, D; Chatters, L; Johnson-Lawrence, V
Abstract: Chronic physiological distress accelerates biological aging and is linked to chronic disease and premature mortality. Physiological distress biomarkers, such as cortisol, represent a key proximal outcome of stress and coping processes through which social inequities are posited to generate health disparities. This study explored how variations in coping may contribute to documented racial disparities in chronic physiological distress between midlife and older Black and White male participants in the National Survey of Midlife Development in the United States (MIDUS) II and the National Study of Daily Experiences (NSDE) II. Black and White men generally reported using similar coping strategies, though Black men relied more on positive reinterpretation, denial, drug use, and physical inactivity than White men. Of the 12 coping strategies examined, ten were unrelated to men's chronic physiological distress levels. Religious and spiritual coping appeared protective, but only for White men. Black men who reported drug use (i.e., illegal drugs, prescription drug misuse) had less chronic physiological distress than those who abstained; drug use was unrelated to White men's distress. Findings suggest that how older adult men cope may not be an important determinant of whether they exhibit chronic physiological distress. Our evidence also does not support conventional categorization of coping strategies as "good" or "bad." Reducing racial health disparities among men may instead necessitate mitigating sources of stress implicated in chronic physiological distress, such as racism. More research investigating our unanticipated findings holds promise for developing targeted interventions to reduce racial disparities in chronic physiological distress among men.